Nekaj o stratigrafiji pri arheoloških raziskovanjih - Korošec, Josip (Arheološki vestnik, 1956)
To day one atrib u tes special im portance to the vertical stratig rap h y . H ow ever, in m any respect such stratigraphy is g reatly insufficient. In m ost cases one finds various vacua in the research w ork, because one investigates single sectors not the whole locality. Therefore, the lacking culture phases come to light la ter on in o th er localities of th e same cu ltu re group and are often in te r[1]p reted incorrectly. Besides a vertical stratig rap h y there exists a horizontal one too in the places w here life was not restricted in a narrow er sense b u t took a m ore extensive course. In such cases the settlem ent was not renew ed in the old place but moved in one o r other direction so as to be renew ed quite close to the old .settlem ent. W hile, in such cases, in some places, there a re gaps in continuity, we m ay state in some cases that, in the perip h ery of renew ing, cul[1]tu ra l rem ains of an older phase are m ingled w ith rem ains of a la te r phase. D efectivness or gaps in continuity could be cleared aw ay by investigating th e w hole localities both those w ith vertical and those w ith horizontal strati[1]graphy. N evertheless, stratig rap h y w ithout typological and o th er investigations cannot give a clear exposition of facts.